(untitled) (Research, Society and Development, 2026)
Oral health in Brazil still faces significant challenges, with dental extractions being prioritized over conservative treatments that preserve functional teeth. This study aimed to analyze the proportion of extractions performed in Piraquara-PR, a municipality in the Metropolitan Region of Curitiba, and compare it with other G100 municipalities, defined as those with more than 80,000 inhabitants considered socioeconomically vulnerable. This is a cross-sectional ecological study based on data from the Primary Health Care Information System (SISAB), covering the period from March 2024 to February 2025, and correlating the results with variables such as the Municipal Human Development Index (MHDI), Gini coefficient, coverage of oral health teams, and the presence of Dental Specialty Centers (CEOs). Seventy-four municipalities were analyzed, with Piraquara presenting an extraction rate of 15.95%, classified as “regular.” A positive correlation was observed between extraction rates and income inequality (Gini), and a negative correlation with MHDI and the presence of CEOs, indicating that more developed municipalities with specialized services perform fewer extractions. Coverage of oral health teams showed no significant association with extraction rates. The results indicate that even among socioeconomically similar municipalities, there are substantial differences in dental practices, highlighting the need for public policies aimed at expanding specialized services and promoting preventive care to reduce mutilating procedures and improve population oral health.